The Audience-Tuning Effect of Negative Stereotypes in Communication - Ye, Junhui; Zhao, Lei; Huang, Zijuan; Meng, Fanxing (Frontiers in Psychology, 2021)
Shared reality theory states that people allow others to influence their own judgments and behaviors when a shared reality is achieved (Hardin and Higgins, 1996; Echterhoff et al., 2009a). Based on this theory, this research has explored how audience attitude affects the communicator’s memory of negative stereotype-related information in interpersonal communication. Two experiments have been conducted, using the negative stereotypes of Chinese “rich second-generation” as the research materials. The results show that the audience-tuning effect of negative stereotypes does in fact occur in interpersonal communication. The participants have tuned their descriptions of both stereotype-related and neutral information to suit their audience’s attitude toward the target. The audience-tuning affects the participants’ recall valence of stereotype-related information while not affecting the recall valence of neutral information. The relational motivation moderates the effect of audience-tuning on the communicator’s memory of stereotype-related information. Only participants who communicated with a desired audience displayed an audience-congruent memory bias of stereotype-related information. The results of this research reveal the bidirectional nature of stereotype-sharedness in interpersonal communication. In actual interpersonal communication, the audience could express a positive attitude toward the target who suffers from negative stereotypes, and the communicator would then convey and recall the stereotype-related information in a more positive manner based on the audience-tunning effect, which could ultimately help to decrease negative stereotypes in communication.